The Role of the Animation Film "Kanca Cilik” in Increasing Student's in Relation to Mental Health Help-Seeking Behaviour - Ahmad Guntur; Lani Tiara Karlina Putri (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: Mental health problems in adolescents or grade school students saw an increased prevalence in 2018 compared to 2013. Some causes of such an increase were poor knowledge and low self-efficacy in relation to help-seeking behaviour in adolescents, especially those attending rural schools. Preventive and promotive efforts can be applied to increase knowledge and self-efficacy in relation to help-seeking behaviour in adolescents. Using a film for health promotion is highly suitable for altering the behaviour of adolescents. Objective: This study aims to analyse differences in the levels of mental health knowledge and self-efficacy among students in rural schools in relation to help-seeking behaviour using the animated film "Kanca Cilik." Methods: This study used a quasi-experimental, time-series design and a control group. The population of this study consisted of 156 students aged 12–19 years who attended rural schools. Samplingwas conducted using the purposive sampling technique. Results: The characteristics of respondents of the intervention and control groups had a p value > 0.05. The knowledge and self-efficacy of the intervention group in relation to help-seeking behaviour had a p value < 0.05. Meanwhile, the knowledge and self-efficacy of the control group in relation to help-seeking behaviour had a p value > 0.05. Conclusion: There was an equality of respondent characteristics in the intervention and control groups. There was a difference in the mean values before and after film screening intervention, but there was no difference in the control group.